Landscapes on the edge: examining the role of climatic interactions in shaping coastal watersheds using a coastal–terrestrial landscape evolution model. Issue 3 (2nd October 2014) - Hackney, Christopher; Darby, Stephen E.; Leyland, Julian
Abstract Incised coastal gullies (ICGs) are dynamic features found at the terrestrial‐coastal interface. Their geomorphic evolution is driven by the interactions between processes of fluvial knickpoint migration and coastal cliff erosion. Under scenarios of future climate change the frequency and magnitude of the climatological drivers of both terrestrial (fluvial and hillslope) and coastal (cliff erosion) processes are likely to change, with an adjunct impact on these types of coastal features. Here we explore the response of an incised coastal gully to changes in both terrestrial and coastal climate in order to elucidate the key process interactions which drive ICG evolution. We modify an extant landscape evolution model, CHILD, to incorporate processes of soft‐cliff erosion. This modified version, termed the Coastal‐Terrestrial‐CHILD (CT‐CHILD) model, is then employed to explore the interactions between changing terrestrial and coastal driving forces on the future evolution of an ICG found on the south‐west Isle of Wight, UK. It was found that the magnitude and frequency of storm events will play a key role in determining the future trajectory of ICGs, highlighting a need to understand the role of event sequencing in future projections of landscape evolution. Furthermore, synergistic (positive) and antagonistic (negative) interactions were identified between coastal and terrestrial parameters, such as wave height intensity and precipitation duration, which act to modulate the impact of changes in any one parameter. Of note was the role played by wave height intensity in driving coastal erosion, which was found to play a more important role than sea‐level rise in determining rates of coastal erosion. This highlights the need for a greater focus on wave height in studies of soft‐cliff erosion. Copyright © 2014 John Wiley & Sons, Ltd.